An Evaluation of Exceptional Civil Service - Bucaktepe, Adil; Coşkun Mert, Nilüfer (Fakultas Syariah dan Hukum, UIN Syarif Hidayatullah Jakarta, 2025)
The Constitution of the Republic of Türkiye states that every Turkish citizen has the right to enter public service and that, in recruitment to the service, there will be no discrimination other than those features required by the position. The Constitution also states that civil servants and other public officials will perform the primary and permanent duties of public service, and that their qualifications, appointments, duties, powers, rights, and obligations will be regulated by law. In this framework, the legal status of civil servants is regulated by the Civil Servants Law no.657. According to this law, those wishing to be appointed to the civil service must meet general and specific conditions, in addition to passing the civil service entrance examination. However, the Civil Servants Law introduced some different regulations for exceptional civil service. The exceptional civil servant positions are listed as restrictions in Article 59. Accordingly, regardless of the provisions for predicted appointments, examination results, staff progression, and promotion grades, appointments can be made to exceptional positions, of which there are a great many, such as parliamentary and ministerial civil servants, some specialists and specialist assistants, ministerial advisers, private secretary directorates, embassy and consulate personnel, and members of the Supreme Council for Religious Affairs. This provision may be used for purposes other than those for which it was intended. Therefore, subjecting the appointment of civil servants to objective criteria will both eliminate this possibility and ensure the provision of public services of the required quality and sufficiency.